Organizatsionno-provovye formy fizkul'turnykh organizatsii v sovremennykh usloviyakh - Voronin, S. E.; Filippov, S. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper is to consider the main organizational-leagal forms of physical culture organizations giving various sporting service. The authors analyze the organizational-structural component of the physical culture movement as well as the organizational-leagal forms of physical culture organization and the organizational leagal forms of their existence.